E Efektivitas Program Campus on Duty (CoD) dalam Meningkatkan Literasi Numerasi Siswa Sekolah Dasar: Efektivitas Program Campus on Duty (CoD) dalam Meningkatkan Literasi Numerasi Siswa Sekolah Dasar - amara saida; Saida, Amara; Santi , Novi Nitya; Sahari, Sutrisno; Aka, Kukuh Andri; Hunaifi, Abdul Aziz; Zaman, Wahid Ibnu (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2024)
The Campus on Duty program is one of the initiatives of Universitas Nusantara PGRI Kediriin collaboration with the Kediri Regency government which aims to improve the quality ofeducation in elementary schools, especially in Kediri or less developed regency areas. One ofthe main focuses of this program is to improve the literacy and numeracy of elementary schoolstudents. This article discusses the effectiveness of the Campus on Duty (CoD) program inimproving students' literacy and numeracy skills at elementary school level. Based on theresults of studies from various journal sources, this program is proven to have a positiveimpact on the basic skills possessed by students, although there are still several challengesfaced, such as limited time and resources. Therefore, it is important to carry out furtherevaluation and development so that this program can be more optimal in its achievements.This research also provides recommendations for improving the quality of programimplementation, both in terms of teacher development, implemented curriculum, and supportfrom the government and community